2015
DOI: 10.1097/aci.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine DNA glycosylase-1-driven DNA base excision repair

Abstract: Purpose of review To provide both an overview and evidence of the potential etiology of oxidative DNA base damage and repair-signaling in chronic inflammation and histological changes associated with asthma. Recent findings Asthma is initiated/maintained by immunological, genetic/epigenetic and environmental factors. It is a world-wide health problem, as current therapies suppress symptoms rather than prevent/reverse the disease, largely due to gaps in understanding its molecular mechanisms. Inflammation, ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…We have chosen lungs as it forms a barrier between environment and vertebrate organisms and its decreased function impacts entire health e.g., correlates with poorer cardiovascular performance, cognitive activities and increased subcortical atrophy, and dementia in humans (Carvalhaes-Neto et al, 1995; Janssens, 2005). In addition, environmental pollutants, osmotic, mechanical stress, and oxidative burst by immune cells in airways leads to 8-oxoG formation, consequently OGG1-BER rev in (Ba et al, 2014; Ba et al, 2015; Bacsi et al, 2016; Radak and Boldogh, 2010). Challenge of lungs with 8-oxoG base robustly increases in GTP-bound levels of KRAS but not activation of HRAS or NRAS in line with previous observations (Aguilera-Aguirre et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have chosen lungs as it forms a barrier between environment and vertebrate organisms and its decreased function impacts entire health e.g., correlates with poorer cardiovascular performance, cognitive activities and increased subcortical atrophy, and dementia in humans (Carvalhaes-Neto et al, 1995; Janssens, 2005). In addition, environmental pollutants, osmotic, mechanical stress, and oxidative burst by immune cells in airways leads to 8-oxoG formation, consequently OGG1-BER rev in (Ba et al, 2014; Ba et al, 2015; Bacsi et al, 2016; Radak and Boldogh, 2010). Challenge of lungs with 8-oxoG base robustly increases in GTP-bound levels of KRAS but not activation of HRAS or NRAS in line with previous observations (Aguilera-Aguirre et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates on the absolute numbers of genomic 8-oxoG lesions in airways (nasal, bonchial, bronchiolar epithelium, or subepihelial lung tissues) which directly interact with the environment is not available; however, the levels of the OGG1-BER repair products (e.g., 8-oxoG base) in serum or urine correlates well with dose and length of exposure, chemical composition, and physical nature of the inhaled environmental agents (Ba et al, 2014; Ba et al, 2015). Moreover, an increase free 8-oxoG levels in sputum and bronchoalveolar lavage fluid after environmental exposures (Ba et al, 2014; Bacsi et al, 2016; Proklou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to considering OGG1 as a target of small molecule inhibition to augment chemo- and radiotherapeutic strategies, a series of insightful studies have revealed the role of OGG1 in the control of airway inflammation as typified in asthma pathogenesis (reviewed in ref 31). Investigations of the modulation of pulmonary inflammation in Ogg1 −/− and knocked down mice have been reported using ovalbumin or ragweed pollen extract as pro-inflammatory challenges.…”
mentioning
confidence: 99%
“…IL-13 is a Th2 cytokine that, when overexpressed in the lung, results in oxidative damage to peripheral blood cells (161). Of note is that oxidized guanidine perpetuates the inflammatory response (162). A related inflammatory mechanism could be present with complexes of oxidized high-mobility group box protein 1, which has been shown to induce hyperoxia-mediated lung inflammation (136,163).…”
Section: Oxygen Perturbation Of Proper Lung Development and Innate Immentioning
confidence: 99%